Challenges and Strategies In Implementing The Minimum Age Limit for Marriage of 19 Years in the Work Area of the Ministry of Religious Affairs of Barru Regency - M. Risa; Muhammad Arif; Oneng Nurul Bariyah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The implementation of the new minimum marriage age of 19 years for both males and females, as specified in Law No. 16 of 2019, faces various challenges in Indonesia, particularly in regions with strong cultural and religious traditions. This study examines the challenges and strategies in implementing this new age requirement in the working area of the Ministry of Religious Affairs in Barru Regency, South Sulawesi. Using a qualitative approach involving in-depth interviews, focus group discussions, document analysis, and field observations, the research explores the perspectives of religious leaders, government officials, community members, and relevant stakeholders. The findings reveal complex interplays between legal reforms, cultural norms, religious interpretations, and socio-economic factors. By incorporating insights from scholars such as Arskal Salim, Siti Ruhaini Dzuhayatin, and others, the study contributes to the discourse on child marriage prevention and offers practical recommendations for effective implementation within the specific regional context. The research highlights the importance of a multi-faceted approach that combines education, legal enforcement, economic empowerment, and cultural sensitization to address the issue of child marriage comprehensively.